Study of the Effect of Centrifugal Force on Rotor Blade Icing Process - Zhengzhi Wang; Chunling Zhu (International Journal of Aerospace Engineering)
In view of the rotor icing problems, the influence of centrifugal force on rotor blade icing is investigated. A numerical simulation method of three-dimensional rotor blade icing is presented. Body-fitted grids around the rotor blade are generated using overlapping grid technology and rotor flow field characteristics are obtained by solving N-S equations. According to Eulerian two-phase flow, the droplet trajectories are calculated and droplet impingement characteristics are obtained. The mass and energy conservation equations of ice accretion model are established and a new calculation method of runback water mass based on shear stress and centrifugal force is proposed to simulate water flow and ice shape. The calculation results are compared with available experimental results in order to verify the correctness of the numerical simulation method. The influence of centrifugal force on rotor icing is calculated. The results show that the flow direction and distribution of liquid water on rotor surfaces change under the action of centrifugal force, which lead to the increasing of icing at the stagnation point and the decreasing of icing on both frozen limitations.